2020
DOI: 10.2217/pgs-2020-0076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Current Level of Pharmacists’ Pharmacogenomics Knowledge and its Impact on Pharmacogenomics Implementation

Abstract: The pharmacists’ role is potentially vital in the growing field of personalized medicine, and well-defined guidelines and knowledge that support this role need to be established. To address the knowledge gap, over the past two decades, pharmacy schools have started providing pharmacogenomics-related courses, a field that overlaps with pharmacy and personalized medicine. Given the fact that pharmacists lead 50% of the Clinical Pharmacogenetics Implementation Consortium implementers’ sites, their role can be par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The major barriers identified in the current study include lack of knowledge, lack of guidelines, and lack of reimbursement for pharmacogenomics services. These barriers are similar to those reported in previous studies [ 10 – 12 , 29 ]. Therefore, strategies to overcome these barriers are recommended to improve the participation of community pharmacists in pharmacogenomics services.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The major barriers identified in the current study include lack of knowledge, lack of guidelines, and lack of reimbursement for pharmacogenomics services. These barriers are similar to those reported in previous studies [ 10 – 12 , 29 ]. Therefore, strategies to overcome these barriers are recommended to improve the participation of community pharmacists in pharmacogenomics services.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that more than two-thirds of community pharmacists had no previous pharmacogenomics training, although an overwhelming majority indicated an interest in attending pharmacogenomics training in the future. Lack of knowledge and training in pharmacogenomics has been identified as one of the major barriers to the implementation of pharmacogenomics in clinical practice among healthcare professionals [ 9 11 , 29 ]. The current study found that community pharmacists had moderate knowledge of pharmacogenomics and this does not corroborate the findings of previous studies conducted among pharmacists in Kuwait, Thailand and Saudi Arabia that reported a low knowledge of pharmacogenomics [ 25 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 Pharmacists in particular have played a leading role in the development and implementation of PGx testing at academic medical centers and large health systems. 3 However, the permeation of testing at the community and local level is likely uneven and limited compared to large health systems. In this pragmatic trial, we examined the feasibility of delivering PGx testing in an independent community pharmacy setting and specifically explored community pharmacists’ preparedness and attitudes toward offering PGx testing.…”
Section: Discussionmentioning
confidence: 99%
“…As the evidence for clinical utility of PGx testing continues to expand, so have rapid and accurate testing platforms and commercial interest, leading to debate and exploration about effective options for delivery of PGx testing. 2 Pharmacists are playing a leading role in the delivery of PGx testing [3][4][5][6] and have been proactive in developing training opportunities and core curricula to prepare the pharmacist workforce to participate in this new professional role. [7][8][9] Professional pharmacist organizations and accreditation bodies have also recognized the future role of the practice and have updated pharmacy school curricula so that all pharmacists have a minimal level of exposure to PGx content.…”
Section: Introductionmentioning
confidence: 99%
“…PGx data is an important part of a patient's clinical picture, yet the literature continues to demonstrate that many pharmacists see the value of PGx but do not feel comfortable interpreting the data. [23][24][25][26] Despite many pharmacists not feeling comfortable to utilize the data, the Oath of a Pharmacist includes "I will accept the lifelong obligation to improve my professional knowledge and competence" 27 Multiple continuing education, certificate, degree, toolkit and training programs are available for pharmacists who seek further PGx educational learning opportunities. Pharmacists in multiple settings outside of precision medicine programs need an understanding of the varying levels of evidence for use of PGx data within clinical care and resources to help apply the data such as CPIC, the Pharmacogenomics Knowledgebase (PharmGKB), the Dutch Pharmacogenetics Working Group (DPWG) and United States Food and Drug Administration (FDA) tables of PGx information.…”
Section: Introduction and Background Of Pharmacogenomics Across Health-care Settingsmentioning
confidence: 99%